MEDIA EDUCATION - AS A SUPPORTING DIRECTION OF PEDAGOGY TO SUPPORT THE STUDY OF "PUBLIC COMMUNICATION" FORMS - Khaydarov Okhinjon Murodjonovich (Bright Mind Publishing, 2025)
The article reveals the content of media education as a direction of pedagogy that supports the study of "mass forms of communication". Highlighted the main tasks of media education.
Keywords: Media, education,